2010
DOI: 10.1016/j.neuropharm.2009.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Age-related LH surge dysfunction correlates with reduced responsiveness of hypothalamic anteroventral periventricular nucleus kisspeptin neurons to estradiol positive feedback in middle-aged rats

Abstract: Female reproductive aging in rats is characterized by reduced gonadotropin releasing hormone (GnRH) neuronal activation under estradiol positive feedback conditions and a delayed and attenuated luteinizing hormone (LH) surge. The newly identified excitatory neuropeptide kisspeptin is proposed to be a critical mediator of the pubertal transition and the ovarian steroid-induced LH surge. We previously showed that estradiol induces less kisspeptin mRNA expression in the anterior hypothalamus [anatomical location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 36 publications
4
46
0
1
Order By: Relevance
“…Recently, moreover, not only the alteration in the LH surge, but also attenuation of KiSS1/GPR54 signaling in the hypothalamus of middle-aged rats have been reported in several articles [28,29,41], suggesting depression of kisspeptin neuron might be a trigger for age-related LH surge dysfunction and reproductive aging [28]. In the present study, we confirmed the similar serial dysfunction of the kisspeptin neuron and LH surge in young adult animals neonatally exposed to EE.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, moreover, not only the alteration in the LH surge, but also attenuation of KiSS1/GPR54 signaling in the hypothalamus of middle-aged rats have been reported in several articles [28,29,41], suggesting depression of kisspeptin neuron might be a trigger for age-related LH surge dysfunction and reproductive aging [28]. In the present study, we confirmed the similar serial dysfunction of the kisspeptin neuron and LH surge in young adult animals neonatally exposed to EE.…”
Section: Discussionsupporting
confidence: 89%
“…Since no abnormalities in ovarian follicles were detected in these animals, disruption of the HPG axis, especially of the luteinizing hormone (LH) surge and hypothalamic KiSS1/GPR54 signaling are predicted. In fact, there are a few reports that show a significant decrease in KiSS1 mRNA expression and kisspeptinimmunoreactivity in the hypothalamic kisspeptin neurons in middle-aged rats [28,29] and in animals neonatally exposed to various estrogenic compounds [30][31][32]. However, the selected dose in these reports are extremely high, and sufficient to cause the "masculinization" of the female brain; therefore, the contribution of kisspeptin to the occurrence of delayed effects induced by low-dose neonatal exposure to estrogenic compounds remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, cumulus and mural GCs have been shown to reflect the characteristics of the oocyte thus providing a noninvasive means to assess oocyte quality [35]. Our current findings suggest that in an infertile population, agerelated upregulation in kiss1r expression may alter kisspeptin sensitivity in human cumulus GCs indicating a possible agerelated physiologic role, similar to that observed in the hypothalamus [7,8], for the kisspeptin system in human follicular dynamics. These findings were supported by current data from mice where old mice had significantly higher kiss1 and kiss1r in their ovaries compared to younger reproductive-aged mice.…”
Section: Discussionsupporting
confidence: 61%
“…We and others have documented that reproductive aging is characterized by reduced hypothalamic kiss1 expression [7,8]. On the other hand, women with diminished ovarian reserve have a significant increase in ovarian sympathetic nerve fibers [9] whose stimulation with β-adrenergic agonist induces ovarian kiss1 expression [4].…”
Section: Introductionmentioning
confidence: 98%
“…3, 6, and 39), a diminished diurnal rhythm of suprachiasmatic nucleus input (17), and reduced responsiveness to kisspeptin (18). However, there is considerable evidence that estrogen positive feedback in women is mediated primarily at the pituitary, with hypothalamic GnRH secretion playing only a permissive role (14,15,21).…”
Section: Discussionmentioning
confidence: 99%